2012
DOI: 10.1124/jpet.111.190249
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from Glycerol-Induced Acute Kidney Injury Is Accelerated by Suramin

Abstract: Acute kidney injury (AKI) is a common and potentially lifethreatening complication after ischemia/reperfusion and exposure to nephrotoxic agents. In this study, we examined the efficacy and mechanism(s) of suramin in promoting recovery from glycerol-induced AKI, a model of rhabdomyolysis-induced AKI. After intramuscular glycerol injection (10 ml of 50% glycerol per kilogram) into male Sprague-Dawley rats, serum creatinine maximally increased at 24 to 72 h and then decreased at 120 h. Creatinine clearance (CrCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
64
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 59 publications
(78 reference statements)
9
64
1
2
Order By: Relevance
“…Previous studies show [21] that renal TGF-β1 expression 48 h after im glycerol injection in mice is 1.5 times greater than our results indicate. It is important to note that the lineage of the animals used was different and that the endogenous gene studied was also different.…”
contrasting
confidence: 57%
See 2 more Smart Citations
“…Previous studies show [21] that renal TGF-β1 expression 48 h after im glycerol injection in mice is 1.5 times greater than our results indicate. It is important to note that the lineage of the animals used was different and that the endogenous gene studied was also different.…”
contrasting
confidence: 57%
“…In mice, particularly male C57Bl/6 mice, the normal serum creatinine level (SCr) is approximately 0.8 ± 0.1 mg/dL [20] , which is similar to the values found in the control groups (Table 1). In a recent study [21] , the authors showed using the glycerol model in rats, that the peak of renal function impairment occurs between 48 and 72 h, as evidenced by SCr levels. In our study, we investigated the peak of injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ARF was induced by intramuscular injection single doses of glycerol (10 ml/kg) into both the hind limbs in equal volume [33].…”
Section: Induction Of Arfmentioning
confidence: 99%
“…In this regard, delayed administration of suramin, a drug that has been used extensively in humans to treat trypanosomiasis, was recently shown to decrease renal injury in various animal models of acute kidney injury and renal inflammation and fibrosis in chronic kidney disease (Zhuang et al, 2009;Liu et al, 2011a;Korrapati et al, 2012). Because patients with DN usually have some degree of renal inflammation and fibrosis (Mathew et al, 2011;Najafian et al, 2011), it would be clinically useful if delayed administration of suramin prevents inflammation and fibrosis.…”
Section: Introductionmentioning
confidence: 99%